METRONIDAZOLE ASSOCIATED SIDE EFFECT IN CEREBELLUM: A CASE REPORT - Naila Younus; Shumaila Younus; Muhammad Ali; Kashif Shazlee (ziauddin University, 2024)
We interpret a case, manifesting Magnetic Resonance (MR) imaging features in relation with Metronidazole (Flagyl) toxicity. MRI brain exhibited an abnormal signal intensity comprising symmetrically bilateral dentate nuclei of cerebellum. The metronidazole toxicity was identified on MR imaging characteristics and reinforced on a clinical basis. In the hospital, metronidazole was stop. Patient recovered clinically with cessation of metronidazole. Follow-up MR imaging was not performed. In this report, we present a case establishing a characteristic finding in MR images within the dentate nuclei of cerebellum. Patient was treated for liver abscess and presented with slurring of speech, generalized weakness, and dysarthia.